Developing workplace injury index (WII) as a measure of safety and health performance in the construction industry in Malaysia - Ali, Hassan; Subramaniam, Chandrakantan; Sri Ramalu, Subramaniam; Mohd Shamsudin, Faridahwati; Ibrahim, Hadziroh; Abd Aziz, Fadzli Shah (Universiti Utara Malaysia Press, 2014)
The construction industry has been identified as one of the main catalysts for growth and accomplishment towards the country’s aspiration to become a developed nation by 2020.However, the increasing trend of fatality in the construction industry has triggered a need for research to address the issue.Research has tended to focus on identifying the trends and types of injuries commonly observed in the construction industry. To date, however, no study to develop a specific measure of occupational safety and health performance in the construction industry especially in Malaysia has been carried out. It is unfortunate that, given the significance of OSH management at the workplace, serious academic attention has been neglected on such an important issue.As such, this study intends to fill in this important gap by attempting to develop an OSH performance measure that provide an indication of the safety and health level of employees in the workplace in the construction industry. This study identified three research objectives namely to identify common injuries in the construction sector, rank the common injuries in the construction sector based on severity of the injury and formulate a Workplace Injury Index as a measure of safety performance in the construction industry.A sample of 72 occupational health doctors registered with the Department of Occupational Safety and Health undertook the process of ranking 30 common injuries in the construction industry.The rankings were done using a scale of 1 (Not Severe) to 30 (Extremely Severe).The Thurstone’s Discriminate Model was then used to develop an internal scale for severity of injury with 1= Not Severe and 30= Extremely Severe. The results of the severity ranking indicated the 5 least severe injuries were scratch, abrasion, bruise, blister, laceration and the 5 most extremely severe injuries are crushing of lower limb, deep burn (< than 50%), electrical shock, deep burn (> than 50%) and asphyxia. Based on the result of the final ranking derived through the Thurstone’s Discriminate Model, Workplace Injury Index (WII) was developed.The WII for the construction industry is WII = 1X1 (n)+ 2X2 (n) + 3X3 (n) + …+ 30X30 (n), where X1-X30 are the injuries ranked according to severity and n is the frequency of the respective injuries.This WII can now be used as a measure of determining safety performance in the construction industry.